Rates of chemical weathering of rocks and minerals - Colman, Steven M; Dethier, David P. (David Putnam), 1950- (Orlando : Academic Press, 1986)
Researchers in geomorphology, geochemistry, Quaternary geology, soil science, and mineralogy will welcome this volume, the first to focus exclusively on rates of silicate chemical weathering. Consisting largely of previously unpublished data from six countries, the volume examines the latest experimental, modelling, and field results.****New information is presented on topics of current research interest, including inferences about chemical mechanisms at the level of mineral surfaces, and data relating weathering rates to landscape evolution over millions of years. The volume integrates the variety of approaches used by diverse subdisciplines in the assessment of weathering rates, and provides up-to-date references.
S.M. Colman and D.P. Dethier An Overview of Rates of Chemical Weathering Kinetics and Mechanisms of Weathering Reactions R.A. Eggleton The Relations between Crystal Structure and Silicate Weathering Rates D.E. Grandstaff The Dissolution Rate of Forsteritic Olivine from Hawaiian Beach Sand G.R Holdren Jr. and P.M. Speyer Stoichiometry of Alkali Feldspar Dissolution at Room Temperature and Various pH Values J.B. Laronne Rate Limitation and Dissolution of Highly Soluble Minerals Rates of Mineral Alteration in Soil Environments R.D. Hall and R.E. Martin The Etching of Hornblende Grains in the Matrix of Alpine Tills and Periglacial Deposits W.W. Locke Rates of Hornblende Etching in Soils on Glacial Deposits Baffin Island Canada W.C. Mahaney and D.L. Halvorson Rates of Mineral Weathering in the Wind River Mountains Western Wyoming D.B. Nahon Evolution of Iron Crusts in Tropical Landscapes F.C. Ugolini Processes and Rates of Weathering in Cold and Polar Desert Environments Weathering of Volcanic Ashes and Deposits R.H. King Weathering of Holocene Airfall Tephras in the Southern Canadian Rockies D.J. Lowe Controls on the Rates of Weathering and Clay Mineral Genesis in Airfall Tephras: A Review and New Zealand Case Study. V.E. Neall and I.K. Paintin Rates of Weathering of 14C-Dated Late Quaternary Volcaniclastic Deposits in the Western United States A.F. White, L.V Benson and A. Yee Chemical Weathering of the May 18 1980 Mount St. Helens Ash Fall and the Effect on the Iron Creek Watershed Washington: Rates of Formation of Rock-Weathering Features S.M. Colman Levels of Time Information in Weathering Measurements with Examples from Weathering Rinds on Volcanic Clasts in the Western United States R. Crook Jr. and A.R. Gillespie Weathering Rates in Granitic Boulders Measured by P-Wave Speeds I. E. Whitehouse, M.J. McSaveney, P.L.K. Knuepfer and T.J.H. Chinn Growth of Weathering Rinds on Torlesse Sandstone Southern Alps New Zealand: Hydrochemical Studies of Rates of Weathering M.A. Velbel The Mathematical Basis for Determining Rates of Geochemical and Geomorphic Processes in Small Forested Watersheds by Mass Balance Examples and Implications J.L. Clayton An Estimate of Plagioclase Weathering Rate in the Idaho Batholith Based upon Geochemical Transport Rates J. Creasey, A.C. Edwards, J.M Reid D.A. MacLeod and M.S. Cresser The Use of Catchment Studies for Assessing Chemical Weathering Rates in Two Contrasting Upland Areas in Northeast Scotland D.P. Dethier Weathering Rates and the Chemical Flux from Catchments in the Pacific Northwest U.S.A. T. Pa*afces Rates of Weathering and Erosion Derived from Mass Balance in Small Drainage Basins M.J. Pavich Processes and Rates of Saprolite Production and Erosion on a Foliated Granitic Rock of the Virginia Piedmont Each chapter includes references Index.
Includes bibliographical references and index
Keywords: Chemical weathering; Geological time